Bilinear-pairing-based remote user authentication schemes using smart cards - Pathan, Al-Sakib Khan; Hong, Choong Seon (ACM New York, 2009)
This paper presents a detailed review of remote user authentication schemes with smart cards based on bilinear pairings. The first scheme regarding this was proposed by Manik et al. in 2006, which had been modified and improved later in several ways. Here, we analyze all the related proposed schemes, point out their weaknesses and flaws, and note down the sequence of improvements. After reviewing all the relevant schemes, we propose our scheme which is designed in such a way that it could ensure all sorts of facilities needed for remote user authentication procedure and could resist all types of known attacks. We present detailed validation, security, and performance analysis to prove the efficiency of our scheme.